Computer-based medical guidelines and protocols : a primer and current trends - Teije, Annette ten; Miksch, Silvia; Lucas, Peter, 1955- (Studies in health technology and informatics ;, 2008)
The book consists of two parts. The first part consists of 9 chapters which together offer a comprehensive overview of the most important medical and computer-science aspects of clinical guidelines and protocols. The second part of the book consists of chapters that are extended versions of selected papers that were originally submitted to the ECAI-2006 workshop 'AI Techniques in Health Care: Evidence-based Guidelines and Protocols.'